Version reckoning of variant glenoid levels: a radiological study on dry human scapulae - Elshahhat, Amr; Abdel Aziz, Aya Mohammed; Basyoni, Yehia; Nour, Khaled Ayman (International Journal of Research in Orthopaedics, 2022)
Background: Preoperative glenoid version measurement can guide base plate implantation and directing screws positioning. Glenoid vault depth affects guide-wire insertion with accurate inclinations towards maximum bone stock. No consensus exists regards the precise glenoid level for version assessment, whether at midaxial or coracoid tip level, and if those values are identical or not. Additionally, there is not much data in literature concerning the deepest point of glenoid vault and its proximity to anterior and inferior glenoid surfaces. Thus, we aimed in this study to report glenoid version values at all levels utilizing two different methodologies (Freidman method, vault version method). Additionally, detecting deepest vault point and how much distant from anterior and inferior glenoid aspects. Methods: Sixty dry, unpaired scapulae were scanned with 1.25mm-thick slices. Version was measured at all levels and compared. Axial and coronal slices with greatest vault depth was determined and distance from anterior and inferior glenoid rims were determined. Results: Version method showed significant difference in version at coracoid tip and midaxial levels (p<0.001). Mean versions were 18.2±10.6º and 8.9±6.8º respectively. Also, significant difference was noted between version of upper, middle, and lower thirds, except between middle and lower thirds. A significant difference was evident between both methodologies on comparing version at coracoid tip level (p<0.001). Conclusions: Glenoid version at coracoid tip and midaxial levels are not the same. Correlation of preoperative version values with intraoperative situations might be studied in future studies.